Birds and other creatures in Renaissance literature - Bach, Rebecca Ann (Routledge, Taylor & Francis Group, 2018)
Introduction: inequality for all – Feathers, wings, and souls – The creaturely continuum in A midsummer night's dream – The lively creaturely/object world of The rape of Lucrece – Falstaff and
Literaturverzeichnis: Seite 185-199
Keywords: Shakespeare; William; English literature; Animals in literature; Birds in literature; Human-animal relationships in literature